he effects of NETosis on fibrinolysis in colon cancer patients - A. A. Parshina; N. N. Tsybikov; P. P. Tereshkov; T. M. Karavaeva; M. V. Maksimenya (Бюллетень сибирской медицины, 2022)
Aim. To investigate formation of neutrophil extracellular traps (NETs) and their impact on fibrinolysis in patients with colon cancer.Materials and methods. The study was performed in two groups. The experimental group consisted of patients with stage 2–3 non-metastatic colon cancer (n = 17, average age – 67 years). The control group included healthy volunteers matched by sex and age (n = 30, average age – 68 years). An experimental model was created from the whole blood. It included platelet-poor plasma and an isolated culture of neutrophils, previously induced to NETosis by adding 100 nmol PMA. The samples were incubated for 4 hours, then the test tubes were centrifuged to pellet cells and their remnants, and the plasma was transferred for subsequent examination. The plasma incubated with intact neutrophils was used as a control. The levels of interleukin-8 (IL-8) and P-selectin glycoprotein ligand-1 (PSGL-1) were used to determine the degree of cell activation. NETosis was confirmed by enzyme-linked immunosorbent assay (ELISA) and fluorescent microscopy. Fibrinolysis was assessed using the thrombodynamics test. The results were compared with the levels of fibrinolytic system components measured by flow cytometry.Results. In the control group, NETosis induction contributed to pronounced neutrophil activation that was accompanied by an increase in the IL-8, PSGL-1, and plasminogen levels, a decrease in PAI-1, and enhancement of fibrinolysis, compared with the intact samples. Higher levels of IL-8, PSGL-1, plasminogen, and PAI-1 and intensified fibrinolysis were detected in the intact samples. However, PMA-induced NETosis did not result in an increase in the degree of activation and significant changes in the given parameters.Conclusion. NETosis promotes both formation and lysis of fibrin clots. However, in cancer patients, suicidal NETosis does not contribute to fibrinolysis due to intracellular protease depletion, which may be one of the mechanisms causing hypercoagulation and insufficient fibrinolysis in cancer.